GROUND DEFORMATION AT CAMPI FLEGREI, ITALY: IMPLICATIONS FOR HAZARD ASSESSMENT - Bellucci F.; Kilburn C.R.J.; Rolandi G.; Woo J. (My University, 2006)
Campi Flegrei caldera, west of Naples in southern Italy, has an exceptional documented record of ground deformation from Roman times onwards. Systematic recording began in the nineteenth century. For earlier dates, information has been obtained from archaeological studies and from contemporary descriptions of the locations of buildings, usually Roman, with respect to sea-level. Especially important have been accounts related to the Serapis, a Roman market-place built in the second century BC and now incorporated within the modern town of Pozzuoli. The long-term patterns of ground deformation have conventionally been investigated on the premise that Campi Flegrei naturally tends to a state of static equilibrium. This study argues that, instead, the area naturally tends to a steady rate of subsidence, at about 17 mm a-1. After this background rate has been removed, the data indicate that a permanent uplift of some 33 m has occurred from Roman times (up until the present day: 2005 at the time of writing), attributable to the intrusion of 1.85 km3 of magma, of which only 1% has been erupted. Uplift has occurred in three episodes, the third of which is still in progress. The behaviour can be interpreted in terms of the intermittent ascent of magma between a reservoir of c. 102-103 km3 at depths of 8-15 km or greater, to a much smaller, shallower system at depths of about 3-4 km. Should the current pattern of deformation follow previous trends, uplift is expected to continue for another 80-90 years, during whieh time Campi Flegrei will be characterized by an elevated possibility of eruption. © The Geological Society of London.